Modelagem e análise experimental de um protótipo didático de motor stirling - Dias, Laura Vitória Rezende (2016)
This work is the development of a prototype for Stirling engine which was designed with the aim of understanding the machine mainly about the component parts, construction difficulties and type of relevant parameters for its performance. Starting from geometric and thermodynamic data from the prototype, with application of the Schmidt modeling, a digital program was developed to calculate values such as power output and efficiency. The prototype was also used to carryd out bench tests using a data acquisition system implemented in electronics platform Arduino Uno. Using Hall-effect and temperature sensors, following the steps of the algorithm proposed by Conner, it was possible to raise data as temperature and revolutions per minute (rpm) for the flywheel coupled to the prototype shaft, these variables made possible to estimate the power output and operational conditions such as the gas temperature in compression and expansion spaces, etc. The comparison between results from simulations and the bench tests demonstrated the great influence of prototype construction data (volumes, source temperature, etc.) on the output power and the performance of the equipment and also how far is the constructed device from the ideal model proposed by Schmidt. The experiments have shown that the prototype can reach a rotation speed up to 1.200 rpm at 159 degrees Celsius of external engine heat source, with output power of 100 milliwatt. The prototype resulting from this research, although small, has allowed the access to important information that can open paths to the construction of larger Stirling engines and consequently with output powers closer to practical use.